2022
DOI: 10.17977/um015v50i22022p247
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of educational applications in assessing the reading skills of junior high school students

Abstract: Utilization of educational applications in assessing the reading skills of junior high school studentsGlobalization and the advancement of technology are giving a new challenge as well as op­portunities for English educators around the globe. Indirectly, there are obstacles associated with learning English due to the fact that technology has become an integral aspect of hu­man existence. The teaching of reading skill also faces the same challenge. Nowadays, read­ing is seen as more important than other skills,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Regarding this, Andriani et al (2018) found that listening learning that utilizes the Spotify application has an impact on students' interest in listening activities and knowing the world that has the same song as the song they are listening to. If students can apply the Spotify application to improve their listening skills, this will greatly help them when taking listening courses in the classroom, as stated by Hidayat et al (2022), using educational apps not only familiarizes students with the digital setting but also motivates them to customize their learning surroundings. This is supported by the answers provided in the preceding section of the questionnaire, both English songs and podcasts on the Spotify application are applications that have helped them improve listening skills.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this, Andriani et al (2018) found that listening learning that utilizes the Spotify application has an impact on students' interest in listening activities and knowing the world that has the same song as the song they are listening to. If students can apply the Spotify application to improve their listening skills, this will greatly help them when taking listening courses in the classroom, as stated by Hidayat et al (2022), using educational apps not only familiarizes students with the digital setting but also motivates them to customize their learning surroundings. This is supported by the answers provided in the preceding section of the questionnaire, both English songs and podcasts on the Spotify application are applications that have helped them improve listening skills.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have revealed that the use of technology has been adopted in testing students' reading comprehension skills. Hidayat et al (2022) found that there are three types of applications used by EFL teachers in designing reading comprehension tests. Those are Google Forms, Canva, and WhatsApp.…”
Section: Mobile Reading Comprehension Testmentioning
confidence: 99%